2022
DOI: 10.1039/d1bm01089a
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation amplitude of hydrogels determines migration, proliferation, and morphology of cells in 3-D culture

Abstract: Fibroblasts spread, migrate and proliferate better in hydrogels with larger stress relaxation amplitude.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In skin bioprinting, either primary skin cells such as fibroblasts, melanocytes, keratinocytes, or stem cells are preferred for the fabrication of skin constructs while maintaining all cellular activities after bioprinting [ 209 ]. Another important property of bio-ink includes viscoelastic behavior that influences the skin bioprintability and also affects the cell migration, proliferation, and remodeling of the ECM [ 210 ]. Regardless of the bio-inks or bioprinting techniques that are utilized, skin bioprinting for wound healing applications is carried out using two strategies, namely ex vivo and in situ bioprinting.…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…In skin bioprinting, either primary skin cells such as fibroblasts, melanocytes, keratinocytes, or stem cells are preferred for the fabrication of skin constructs while maintaining all cellular activities after bioprinting [ 209 ]. Another important property of bio-ink includes viscoelastic behavior that influences the skin bioprintability and also affects the cell migration, proliferation, and remodeling of the ECM [ 210 ]. Regardless of the bio-inks or bioprinting techniques that are utilized, skin bioprinting for wound healing applications is carried out using two strategies, namely ex vivo and in situ bioprinting.…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…A two-step crosslinking process as described in Figure 1 was designed to gradually introduce Ca 2+ ions to the alginate solution, as compared to inactive calcium sources such as CaCO 3 , CaSO 4 , or CaHPO 4 , which were used in previous studies. [15,[25][26][27][28][29][30][31] In the present approach, fully crosslinked Alg or OA HMPs serve as Ca 2+ reservoirs. Compared to directly pre-crosslinking alginate with a CaCl 2 solution, alginate hydrogels were known to release Ca 2+ ions in a diffusion-controlled release pattern, induced by an ion-exchange process.…”
Section: Preparation Of Hmp Pre-crosslinked Inksmentioning
confidence: 99%
“…[15,[25][26][27][28][29] Other studies have shown that internal gelation can successfully be used for the preparation of bioinks. [30][31][32][33][34] It was also found that pre-crosslinking improves alginate printability by reducing the merging of strands and pores [30,[32][33][34] and that it may also be used to improve cell behavior, such as proliferation and migration [31] or to direct mesenchymal stem cell differentiation. [33] These methods invariably require a change in pH in the gels that cannot be tolerated by every type of cells, e.g., considering previous works of the authors, where D-(+)-glucono-1,5-lacton (GDL) was used as acidifier.…”
Section: Introductionmentioning
confidence: 99%
“…It is important that the printed tissue/organ constantly ensures the normal cellular activities, including cell migration capacity and proliferation rate [13]. Indeed, the viscoelastic behaviour of bioinks influences their printability, but also the ability of cells to remodel the matrix, spread, migrate, and proliferate [14].…”
Section: Introductionmentioning
confidence: 99%